Effects of chironomid larvae and Limnodrilus hoffmeisteri bioturbation on the distribution and flux of chromium at the sediment-water interface. (1st September 2019) - Cheng, Dandong; Song, Jinxi; Zhao, Xiaotian; Wang, Shaoqing; Lin, Qidong; Peng, Jianglin; Su, Ping; Deng, Wenjia
Abstract: The impacts of chironomid larvae and the tubificid worm Limnodrilus hoffmeisteri on the distribution and flux of the heavy metal chromium (Cr) across the sediment-water interface were investigated with a 21-day laboratory microcosm experiment. The two studied species feature different bioturbation modes involving bioirrigation and upward bioconveyance. The Cr concentrations in the overlying water and pore water were measured and compared using treatments with bioturbation by a single species and by combinations of both species and a treatment with no organisms. The results indicated that both bioturbation modes significantly increased the Cr concentrations in the overlying water and pore water. The overlying water had lower Cr concentrations than the pore water. Little variation in the Cr concentrations was observed in the treatment without organisms. Both species enhanced the Cr flux from the pore water to the overlying water. The worm treatments had a great impact on the Cr concentration in the overlying water through intensive upward conveyance activity, while the chironomid larvae treatments exerted significant effects on the Cr variation in the pore water and Cr flux across the interface via bioirrigation activity. These findings reveal the importance of bioturbation in biogeochemical processes in freshwater ecosystems. Highlights: Bioturbation facilitate contaminant transport across the sediment-water interface can be a threat to aquatic ecosystem. Different bioturbation activities significantly increased Cr concentration in the overlying water and pore water. The Limnodrilus hoffmeisteri had greater effect on the transport of Cr.